Mapping Status for River Water Quality of Sungai Merbok, Kedah based on DOE-WQI - Ahmad Mukhtar Md Norodin (Penerbit Universiti Malaysia Perlis, 2011)
The purpose of this study is to mapping, trends the status of river water quality index of sungai merbok, Kedah Darul Aman and to determine the levels of key constituents stated in Interim National Water Quality Standard (INWQS). Sungai Merbok Basin generates brackish water by having their river mouth in the ocean and creates a unique environment having mangroves ecosystem considered to be one of the most productive natural ecosystems on earth. Five sampling point have been identify in Sungai Merbok Basin which is upstream, two in the middlestream which is bridge at Sungai Petani river and downstream, the sample will be analyze insitu and exsitu and the behavior of the sample location is observed once a week for a month period. The method of determining water quality is done by using Department of Environmental Water Quality Index (DOE-WQI), it is used to show the value of the water quality of a waterway. Six parameter are use to get the value by calculation which is Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH value, Ammoniacal Nitrogen (AN), and Suspended Solid (SS). The study also conducted to detect the changes in Sungai Merbok water quality as a result of development activities in that area. The result showed that the Water Quality Index (WQI) of Sungai Merbok prone to be slightly polluted in the index range of 60-80. This study also proves that tributaries are the main sources of pollution, contributing point-source and non point-source pollution loading into Sungai Merbok, in which point source is higher compared to non-point pollution sources.